3D-QSAR modeling and pharmacophore study of serotonin 5HT-₂A receptors antagonists - Antonijević Mirjana; Nikolić Katarina; Vučićević Jelica; Oljačić Slavica; Agbaba Danica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Creation of a statistically reliable 3D-QSAR (Quantitative Structure Activity Relationships) model enables definition of the structure of the pharmacophore for antagonists of serotonin 5-HT2A receptors and selection of the key molecular determinants for the design of new antagonists. A 3D-QSAR study was applied on a series of 50 antagonists of 5-HT2A receptors. The data set is divided into the training set, composed of 33 compounds, and test set containing 14 molecules. The training set was used to build the 3D-QSAR model, while test set was used for model validation. This 3D-QSAR study was performed by use of the Pentacle 1.07 programs. Obtained statistical and validation parameters for training set (R²= 0.96; Q²=0.75, RMSEE= 0.211); and for test set (R²pred=0.51; RMSEP= 0.558); indicate on reliability and good predictive potential of the 3D-QSAR model. Based on the most influential variables of the selected 3D-QSAR model, the molecular determinants for the antagonistic effect on the 5-HT2A receptors were selected: hydrogen bond acceptor and hydrogen bond donor at a distance of 10.4A-10.8A (v495: O-N1); carbonyl oxygen and a steric hot spot at a distance of 14.8A-15.2A (v640: N1-TIP); hydrophobic domain and hydrogen bond acceptor at a distance of 3.2A-3.6A (v276: DRY-O); two steric hot spots at a distance of 18.8A-19.2A (v248: TIP-TIP) .